Temporal Changes of Cardiac Structure, Function, and Mechanics During Sub-acute Cervical and Thoracolumbar Spinal Cord Injury in Humans: A Case-Series - Balthazaar, Shane J. T.; Nightingale, Tom E.; Currie, Katharine D.; West, Christopher R.; Tsang, Teresa S. M.; Walter, Matthias; Krassioukov, Andrei V. (Frontiers in Cardiovascular Medicine, 2022)
Individuals with cervical spinal cord injury (SCI) experience deleterious changes in cardiac structure and function. However, knowledge on when cardiac alterations occur and whether this is dependent upon neurological level of injury remains to be determined. Transthoracic echocardiography was used to assess left ventricular structure, function, and mechanics in 10 male individuals (median age 34 years, lower and upper quartiles 32–50) with cervical (n = 5, c-SCI) or thoracolumbar (n = 5, tl-SCI) motor-complete SCI at 3- and 6-months post-injury. Compared to the 3-month assessment, individuals with c-SCI displayed structural, functional, and mechanical changes during the 6-month assessment, including significant reductions in end diastolic volume [121 mL (104–139) vs. 101 mL (99–133), P = 0.043], stroke volume [75 mL (61–85) vs. 60 mL (58–80), P = 0.042], myocardial contractile velocity (S') [0.11 m/s (0.10–0.13) vs. 0.09 m/s (0.08–0.10), P = 0.043], and peak diastolic longitudinal strain rate [1.29°/s (1.23–1.34) vs. 1.07°/s (0.95–1.15), P = 0.043], and increased early diastolic filling over early myocardial relaxation velocity (E/E') ratio [5.64 (4.71–7.72) vs. 7.48 (6.42–8.42), P = 0.043]. These indices did not significantly change in individuals with tl-SCI between time points. Ejection fraction was different between individuals with c-SCI and tl-SCI at 3 [61% (57–63) vs. 54% (52–55), P < 0.01] and 6 months [58% (57–62) vs. 55% (52–56), P < 0.01], though values were considered normal. These results demonstrate that individuals with c-SCI exhibit significant reductions in cardiac function from 3 to 6 months post-injury, whereas individuals with tl-SCI do not, suggesting the need for early rehabilitation to minimize cardiac consequences in this specific population.